Mandibular bilateral macrodontia and hyperdontia: a clinical case report - Rúa-Cardona, Nathalia; Tapias, John Jairo; Castaño-Henao, Jorge Mario (Revista Facultad de Odontología Universidad de Antioquia, 2011)
Macrodontia is a dental size anomaly of unknown etiology, characterized by abnormal tooth size when compared to the rest of the dental formula. Hyperdontia is the presence of an increased number of teeth in the dental formula. Although it is rare, in some cases both anomalies have been reported simultaneously, and they might be associated or not with a syndrome. A 12-year-old male patient who was scheduled for a routine dental exam revealed at the radiographic examination impaction of teeth 34, 35 and 45 with macrodontia of the same teeth and multiple hyperdontia (three extra teeth, located occlusal to 34, 35 and 45); no other relevant pathology was found. Multiple macrodontias and hyperdontias are rare dental anomalies that may cause pathologies and alterations to adjacent permanent teeth.